The Development of Guided Inquiry-Based Studentsâ Worksheet in Cell Material for Senior High School Students - Isnaeni, Lili Astuti; Yuniastuti, Ari; Susanti, R (Journal of Biology Education, 2017)
This research was aimed to develop guided inquiry-based studentsâ worksheet in cell materials forstudents in senior high school. It has the characteristics of valid, readable, and executable. This researchwas a Research and Development (R&D) type. The validity of worksheet was valued by validator andanalyzed using percentage description. The readability of worksheets can be obtained by small scaled tryout to 20 students taken by using purposive random sampling. The executability of worksheets wasobtained by bigger scale try out to 32 students. The result of the research showed that the guided inquirybasedstudentsâ worksheets had characteristics of: 1) cell titled worksheets with its observation; 2) theactivities based on syntax model of guided inquiry learning; 3) the material is related to real example; 4)the illustration picture in worksheets was real and 5) the display of worksheet in full color. The averagepercentage of validity to the worksheet was 83.06%. The percentage score of the worksheet was 85.31%with executability of 93.18%. Based on the results, it can be concluded that this worksheet has severalcharacteristics and valid category to be used. It also had good readability and executability to thestudents.